Astabilizing system for butter pastes based on the dry concentrates of milk protein - Kochubei-Lytvynenko, Oksana; Yatsenko, Olga; Yushchenko (Gonchar), Natalia; Bandura (Kuzmyk), Uliana (My University, 2018)
The composition of the stabilizing system for butter pastes based on dry concentrates of milk and whey proteins has been substantiated; that would help reduce the deficiency of protein in the diet of modern human and would make it possible to further improve the balance of the composition of the butter paste. Considering their functional-technological characteristics, conditions for gelation and synergy, the polysaccharides carrageenan and guar gum were introduced to the composition of the stabilizing system.

Обґрунтовано склад стабілізуючої системи для масляних паст на основі сухих концентратів молочно-сироваткових білків; що сприяло б зменшенню дефіциту білка в харчуванні сучасної людини та дало б змогу ще більше покращити збалансованість складу масляної пасти. Враховуючи їх функціонально-технологічні характеристики, умови гелеутворення та синергію, до складу стабілізуючої системи введено полісахариди карагенан і гуарова камедь.
Keywords: butter paste; milk protein concentrate; whey milk protein; protein–polysaccharide complex; кафедра технології молока і молочних продуктів; кафедра технології ресторанної і аюрведичної продукції; масляні пасти; молочний білковий концентрат; сироватковий молочний білок; білково-полісахаридний комплекс